PERTANGGUNG JAWABAN PIDANA PELAKU AKTIF TINDAK PIDANA PENCUCIAN UANG DALAM HAL PENGEMBALIAN ASET HASIL KORUPSI - Salman Alfarizi Antas; Dwi Andayani Budisetyowati; Diana Fitriana (INTELIGENSIA MEDIA, 2023)
In this study, it aims to analyze a criminal act of money laundering committed by active actors in terms of returning assets resulting from corruption, the process of money laundering carried out by active actors causes something that is very detrimental to the state and bureaucracy. Money laundering is a follow-up crime in which a crime that participates in corruption which is an extra ordinary crime. The research method used is a normative research method with a statutory approach and a case approach. The types and sources of legal materials used are primary, secondary, and tertiary materials using the collection of legal materials. The theoretical framework in this study uses the theory of legal certainty, law enforcement theory, and corruption theory. The conceptual framework in this study uses criminal responsibility of active actors, money laundering, and return of assets resulting from corruption. The results of the research obtained in the conclusions and suggestions of this study are that money laundering is an act that deviates from legal norms and also violates the rules of the law that has been written. And the form of criminal responsibility is that the perpetrators of the crime of laundering must be held accountable for their actions by carrying out the punishment that has been set. The government and law enforcement officials can make a policy that is contained in a form of legislation by prioritizing the effectiveness of the legal product and accompanied by a good legal structure and culture to be able to prevent and eradicate money laundering.